Derrida and Phenomenology
IX, 214 p.
Keywords: Derrida and Phenomenology is a collection of essays by various authors, entirely devoted to Jacques Derrida's writing on Edmund Husserl's phenomenology. It gives a wide range of reactions to those writings, both critical and supportive, and contains many in-depth studies. Audience: Communicates new evaluations of Derrida's critique of Husserl to those familiar with the issues: specialists in phenomenology, deconstruction, the philosophies of Derrida and Husserl. Also contains a bibliography of recent relevant literature.